MENUMBUHKAN MINAT GENERASI MUDA TERHADAP BAHASA DAN SASTRA LAMPUNG MELALUI INOVASI PEMBELAJARAN BERBASIS BUDAYA LOKAL - Icha Giri Palupi; Nadia Aufa (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2025)
The Lampung language and literature are an important part of the cultural identity of the Lampung people, serving as a means of communication, expression, and transmission of noble values. This study aims to identify innovative strategies based on local culture that can foster interest in the Lampung language and literature among the younger generation. The research method used is descriptive qualitative with subjects consisting of teachers, students, and university students, and data collection through interviews, observation, and documentation, which is then analyzed using the Miles and Huberman model. The results of the study show that the main strategies include: (1) integration of cultural values through folk tales and traditional arts activities, (2) contextual learning that links language to everyday situations and traditional activities, and (3) the use of digital technology and social media as modern and interactive learning media. This innovative learning model is expected to improve literacy, creativity, and students' love for Lampung's cultural heritage, so that the preservation of regional languages and literature can be realized sustainably. This study provides theoretical contributions to the development of local culture-based learning and practical benefits for educators in designing creative, relevant, and interesting learning media for the younger generation.